Cardiac parasympathetic activity and race performance: an elite triathlete case study - Stanley, J.; D`Auria, S.; Buchheit, M. (International Journal of Sports Physiology and Performance, 2015)
The authors examined whether changes in heart-rate (HR) variability (HRV) could consistently track adaptation to training and race performance during a 32-wk competitive season. An elite male long-course triathlete recorded resting HR (RHR) each morning, and vagal-related indices of HRV (natural logarithm of the square root of mean squared differences of successive R-R intervals [ln rMSSD] and the ratio of ln rMSSD to R-R interval length [ln rMSSD:RR]) were assessed. Daily training load was quantified using a power meter and wrist-top GPS device. Trends in HRV indices and training load were examined by calculating standardized differences (ES). The following trends in week-to-week changes were consistently observed: (1) When the triathlete was coping with a training block, RHR decreased (ES -0.38 [90% confidence limits -0.05;-0.72]) and ln rMSSD increased (+0.36 [0.71;0.00]). (2) When the triathlete was not coping, RHR increased (+0.65 [1.29;0.00]) and ln rMSSD decreased (-0.60 [0.00;-1.20]). (3) Optimal competition performance was associated with moderate decreases in ln rMSSD (-0.86 [-0.76;-0.95]) and ln rMSSD:RR (-0.90 [-0.60;-1.20]) in the week before competition. (4) Suboptimal competition performance was associated with small decreases in ln rMSSD (-0.25 [-0.76;-0.95]) and trivial changes in ln rMSSD:RR (-0.04 [0.50;-0.57]) in the week before competition. To conclude, in this triathlete, a decrease in RHR concurrent with increased ln rMSSD compared with the previous week consistently appears indicative of positive training adaptation during a training block. A simultaneous reduction in ln rMSSD and ln rMSSD:RR during the final week preceding competition appears consistently indicative of optimal performance.